2001
DOI: 10.1063/1.1371967
|View full text |Cite|
|
Sign up to set email alerts
|

Generic degradation mechanism for 980 nm InxGa1−xAs/GaAs strained quantum-well lasers

Abstract: The effects of interdiffusion on the subbands in Ga x In 1−x N 0.04 As 0.96 / GaAs quantum well for 1.3 and 1.55 μm operation wavelengths J. Appl. Phys. 90, 197 (2001); 10.1063/1.1370110High-temperature optical gain of 980 nm InGaAs/AlGaAs quantum-well lasers

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…Some earlier papers [8]- [11], [20] have revealed a similar white line, as visible in Figs. 2 and 5, by TEM analysis of the defect pattern.…”
Section: Nature Of the White Linesupporting
confidence: 73%
“…Some earlier papers [8]- [11], [20] have revealed a similar white line, as visible in Figs. 2 and 5, by TEM analysis of the defect pattern.…”
Section: Nature Of the White Linesupporting
confidence: 73%
“…The active parts of the laser are destroyed, intermixing between the different layers was reported by different authors, Chu et al [26] showed that In outdiffusion was the main reason for degradation in strained InGaAs/GaAs lasers. Misfit stress was found to not contribute to the compositional instability in strained InGaAs/GaAs systems [27]; in these cases inter-diffusion can take place by the concentration difference between each side of the interface; a similar consideration can be made for AlGaAs/GaAs systems.…”
Section: Catastrophic Degradationmentioning
confidence: 99%
“…A similar dependence was also observed for the threshold current of edge emitting lasers using similar InGaAs/GaAs strained quantum wells. 9 Chu et al 10 Traditionally, others have not considered the initial test period where faster degradation occurs in determining the EOL. The lifetime is estimated using a linear extrapolation (i.e., assuming a constant degradation rate) applied after an arbitrary initial degradation period.…”
Section: Failure Modementioning
confidence: 99%